Profile of Day Case Paediatric Surgical Patients in a Tertiary Care Hospital in Bangladesh - Rahman, SM Mahfuzur; Amin, Md Ruhul; Ahmed, Shamsuddin; Chakraborty, Debashis; Amin, Mohammed Ruhul (Eastern Medical College Journal, 2024)
Introduction:In recent years, the prevalence of Paediatric Day Case Surgery has risen significantly in Western countries. This trend offers notable benefits, including decreased psychological stress for both children and parents, as well as reduced hospital costs, instances of nosocomial infections and the length of surgical waiting lists.This study aimed to assess the profile of day-case paediatric surgical patients in a tertiary care hospital inBangladesh. Materials & Methods: This prospective study was conducted for a period of 6 months from July to December 2014with ethical clearance from respective IERB. A total of 298 surgical operations were performed on infants and children in the paediatric surgery department of Bangabandhu Sheikh Mujib Medical University (BSMMU) having optimum operating, anesthetic and post-anesthetic recovery facilities. Among the patients, 103 patients were undergone as day-case procedures. All data was collected using a pre-formed questionnaire. Collected data were analyzed using descriptive statistics. Analysis of data was carried out by using SPSS V22.0 for Windows. After analysis, the data was presented in tables and charts. Results: The youngest patient was 18 days old and the oldest was 14 years old. The median age was 4.5 years. Males dominated over the females with a ratio of 1.8:1. In the post-operative period, 87.3% of patients required two doses of oral analgesia, with 29.1% returning to normal activity the next day. Complications occurred in 3.6% of patients under 1 year and 8.6% of those over 1 year, with one case of post-operative pneumonia requiring hospitalization. Most surgeries (54.4%) were performed within 2-4 weeks of the first outpatient visit, with an average waiting time of 20 days (SD 6.2 days). Parents generally accepted the outpatient procedure, with 44% suggesting improvements in the waiting room and time, 6.4% fully satisfied, and 2.7% expressing concerns about transportation, post-operative care, and pain management at home. Conclusion: Paediatric day-case surgery is being practiced safely and cost-effectively at BSMMU. Unplanned overnight admissions are low, possibly due to well-selected and well-monitored cases. Children of all age groups, including neonates, are suitable for pediatric day-case surgery. The socio-economic condition and educational status of the caregivers are not a bar for day-case surgery. Eastern Med Coll J. July 2024; 9 (2): 110-114